Study on equal channel angular extrusion of circular cross section components and its application for joining dissimilar metals / Davoud Mashhadi Jafarlou - Davoud Mashhadi, Jafarlou (2016)

(untitled)
In the last two decades, significant focus has been directed toward severe plastic deformation (SPD) as a direct method to produce bulk metals with superior mechanical properties. Numerous researches have been conducted in order to develop SPD methods for grain refinement of metallic structure with various geometrical shapes and chemical compositions. Among these methods, equal channel angular extrusion (ECAE) is the most developed SPD technique due to its capability of processing structural components. The mechanical properties of wide range of pure metals and alloys have been investigated in different research works; however there is a lack of study on mechanical properties of AA 6063 processed by ECAE. Moreover the ECAE technique is used mostly for grain refinement of components with circular (rod) or rectangular (beam) cross sections and there is no robust study on developing this technique for the processing of tubular components. Therefore, the current study focused on developing ECAE for processing tubular components. Additionally, in this research a developed method for solid state joining of dissimilar metals was proposed. In the first phase of this study, the mechanical properties of ECAE treated AA 6063 were investigated. Following the ECAE process, samples were subjected to heat treatment (HT), hard anodizing (HA), and a combination of HT and HA. From the experimental fatigue and fretting fatigue tests, it was apparent that the ECAE treatment improves fatigue and fretting fatigue lives of the samples at low and high-cyclic loads and post ECAE heat treatment (ECAE+HT) more effectively improves the fatigue endurance. HA of AA6063 increased the fatigue and fretting fatigue lives of ECAE + HT-processed samples at low cycle; however, at high cycle, HA had reverse effects, whereby the fatigue and fretting fatigue lives of ECAE + HT-processed samples reduced. iv In the second part of this research ECAE was utilized to produce metal tubes with ultrafine grain (UFG) structures. To mitigate plastic instability effects such as tube buckling and fracture during processing, hydraulic oil was used to fill the tube cavity. Finite element analysis (FEA) was carried out to examine the feasibility of the proposed method and deformation mechanism during ECAE. Experimental test results indicated that the resultant 60% reduction in grain size led to significant mechanical properties improvements including yield shear strength, ultimate shear strength, and microhardness. In the third phase ECAE was applied for the solid state joining of tubular AA 6061 components and SAE 1018 steel rods. The influence of using a 0.1 mm thick 60Ag- 30Cu-10Sn interlayer in addition to annealing at 220, 320, 420 and 520 °C for 60 min was investigated as well. FEA was performed in order to evaluate the deformation behavior of the workpieces during the ECAE joining process. The FEA outcome showed remarkable accumulation of equivalent plastic strain with relatively low strain inhomogeneity. Experimental results revealed that by increasing annealing temperature and using interlayer, the joint strength was improved. According to the results, shear strength of up to 32 MPa is feasible by having an interlayer and with subsequent annealing at 520 °C.